Trans-European-networks and the development of transport in the eastern Baltic Sea region - Claus-Friedrich Laaser (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The European Unions's task of providing Trans-European Networks (TENs) in transportation, communications and energy transmission which has been enacted by the treaty of Maastricht, is not confined to internal networks in the EU. Since 1994 this task has been widened so as to give support to the economies in transition (EIT) in Central and Eastern Europe that have applied for EU membership. These actions are taking place in a variety of different fields. Transport infrastructure upgrading is initiated both in general and with respect to specific links between the EU and the EIT. The international community is supporting network upgrading in all Baltic Rim EIT. Specific infrastructure measures refer to the Pan-European "Crete Corridors", i.e. the links between EU members and associated EIT. Other "hardware" measures are related to the construction of border stations or the promotion of telematics in the whole Baltic Sea Region in order to facilitate freight traffic. On the "software" side, TEN initiatives have been enacted to harmonize infrastructure cross-border planning, in particular for Crete Corridors' supervising committees, to account for network externalities. If one widens the narrow definition of infrastructure to institutions, the adjustment of EITs' transport regulatory systems to EU regulations and competition policy can also be subsumed under the heading of TENs. The purpose of this paper is to evaluate the relative importance of the various measures taken in the course of the TEN initiative in the field of transport for economic development of the EIT on the Eastern shore of the Baltic Sea. The paper considers these actual approaches of European transport policy as well as the needs of the EIT. Though missing infrastructure links and insufficient capacities are more visible, it turns out that "software" problems (both from the sphere of regulatory regimes and from administrative procedures) seem to be the most pressing obstacles to transport and trade in the Baltic Rim. The paper discusses the pros and cons of the various TEN components in transport from the perspective of fiscal federalism and of regional development aid for the EIT. Furthermore it refers to issues of modal split, in particular with respect to Russia (for which the Baltic Rim is an important transit point), and to intermodal competition between land transport and the Baltic sea lane.
Keywords: F15; H54; H77; L91; P20; R48; 330; Verkehrsinfrastrukturpolitik; EU-Politik; Verkehrspolitik; Internationale Wirtschaftsbeziehungen; Verkehrswegepolitik; Finanzföderalismus; Verkehrsträgerwettbewerb; Ostsee; Osteuropa